Letter from Harrison Shull to Robert S. Mulliken, 1959 - Mulliken, Robert Sanderson (1959)
Letter between Harrison Shull and Robert S. Mulliken, American quantum chemists, concerning travel arrangements for Mulliken and colleagues.
Keywords: Shull, Harrison; Biochemists; Platt, John Rader, 1918-; Mulliken, Robert Sanderson; Chemists; Biophysicists; Matsen, F.A. (Frederick Albert), 1914-; Physicists; Nobel Prize winners